Respuesta :

Answer:

x = 9/5

Step-by-step explanation:

We want to combine like terms and isolate the variable (x) from the constants (regular numbers).

Subtract x from both sides:

[tex]6x-9-x=x-x[/tex] ⇒ [tex]5x-9=0[/tex]

Now add 9 to both sides:

[tex]5x-9+9=0+9[/tex] ⇒ [tex]5x=9[/tex]

Divide by 5 from both sides:

[tex]5x/5=9/5[/tex] ⇒ [tex]x=9/5[/tex]

Thus, the answer is x = 9/5.

Hope this helps!

Hey there,

Here's how you solve the following equation:

                        6x - 9 = x

  1. The first step is to subtract 6x from both sides:                                             -9 = -5x
  2. Now we just divide by -5 from both sides:                                                      [tex]\frac{9}{5}[/tex] = x

So the answer to the following equation would be x = [tex]\frac{9}{5}[/tex] .

Hope I helped,

Amna